THE ESTABLISHMENT AND DEVELOPMENT OF QUALITY SYSTEMS OF EDUCATIONAL INSTITUTIONS - Viktor I. Kruglov; Oleg A. Gorlenko; Tatyana P. Mozhayeva (Высшее образование в России)
The paper suggest the methodological approach to increase the efficiency of educational institution activity on the basis of analysis of foreign and Russian experience on creation and development of quality systems. The authors consider the features of formation and improvement of the quality system in educational institutions on the basis of the standard quality system model based on the methodological provisions of the standards and recommendations of ENQA and the standards ISO series 9000 version 2000. In connection with the approval of ISO 9001 : 2015 there is a need to improve the standard quality system model for educational institution. The authors suggest ways to solve this problem basing on the methodological principles of this standard. Special attention is paid to the process approach and leadership of the head. In particular, the feasibility of establishing integrated management systems and quality systems for educational institutions is marked out.